Knowledge of diabetes, its complications and treatment adherence among diabetic patients - B. S., Deepali; Subramanian, Mangala; G., Soumya; B. R., Vikyath; P., Aarudhra; M., Ankitha; R., Deepashree; N., Nagashree (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes Mellitus not only debilitates, but also kills. It may lead to microvascular and macrovascular complications. This study was undertaken a) to assess the knowledge of diabetes and its complications among patients with type 2 diabetes mellitus, b) to assess treatment adherence of the above patients, c) to determine association of knowledge and treatment adherence. Methods: Across sectional study was conducted on a total of 120 patients coming to Vydehi Institute of Medical Sciences and Research Centre, Bangalore over a period of 2 months. A semi-structured questionnaire consisting of questions on patients’ knowledge of diabetes, its complications and adherence to treatment was administered and each patient was interviewed face-to-face. The data was analyzed using SPSS Version 21.0. Statistical analysis was done based on percentages and proportions. Results: Out of 120 diabetics, 67 (55.8%) had more than 80% knowledge regarding diabetes mellitus and its complications, 45 (37.5%) patients had 60-79% knowledge and only 8 (6.7%) patients had less than 60% knowledge. The study revealed that 77 patients (64.2%) scored greater than 80% in the treatment adherence, 27 patients (22.5%) scored between 60-79% and 16 (13.3%) scored below 60%. Patients having more knowledge better adhered to the treatment. Therefore 55.8% of the people who had greater than 80% knowledge, better adhered to their treatment. Conclusions: Patients having more knowledge better adhered to the treatment. This highlights the importance of empowering patients with knowledge regarding the disease to obtain maximum benefit from their treatment.